SUSPECTED MEASLES AND IMMUNIZATION TRENDS BEFORE AND DURING COVID-19 IN EAST JAVA, INDONESIA: Tren Kasus Suspek Campak dan Cakupan Imunisasi Sebelum dan Selama Pandemi COVID-19 di Jawa Timur - Arifin, Munif; Putri Haryanik, Meilinda Alya'; Prasetyowati, Irma (Universitas Airlangga, 2025)
Background: Measles, caused by a virus belonging to the genus morbillivirus of the paramyxoviridae family, remains a global health challenge. The COVID-19 pandemic has affected measles prevention activities. Understanding measles characteristics before and during the pandemic is important to developing effective prevention programs. Purpose: This study aims to analyze measles suspects' epidemiological characteristics before and during the COVID-19 pandemic. Method: This study used a cross-sectional approach. The population in this study were all measles suspects before and during the COVID-19 pandemic. The data sources were the results of tracing measles suspects and the results of examination of BBLK Surabaya measles specimens (measles IgM) before the pandemic (2017-2019) and during the pandemic (2020-2022). The correlation test was carried out using Chi-square analysis. Results: The analysis results indicate the following p-values: age = 0.00, gender = 0.92, immunization status = 0.00, and test lab = 0.46. The findings showed a relationship between age and immunization status regarding suspected measles before and during the COVID-19 pandemic. However, there was no significant relationship between gender and lab results of suspected measles before and during the pandemic. Conclusion: There was a significant relationship between immunization status and age in measles suspects before and during the COVID-19 pandemic. Therefore, optimizing immunization coverage and ensuring immunization is carried out on time according to the specified age is necessary.